FACTORS THAT AFFECT CUSTOMER SATISFACTION (SURVEY ON JNE DELIVERY SERVICE BANGKINANG CITY BRANCH) - Jeng Opli; Mustafa Kamal; Auzar Ali (STIE Bangkinang Publishing, 2021)
This study aims to find out the factors that affect customer satisfaction in JNE Bangkinang Kota Branch delivery services. JNE branch population bangkinang city in 2019 as many as 18,884 people, the population in this study is people in bangkinang city who have visited and used the services of JNE. The sample was determined using accidental sampling method with the number of respondents in this study as many as 100 people with multiple linear regression analysis. The data type used consists of primary and secondary data. The data were collected using questionnaires and research files. From the validity test results, all items of the statement submitted to the respondent are declared valid. Reliability test results also showed that each item item has a good level of reliability with alpha cronbach's value above 0.5. From the results of the study, it can be concluded that variables free of physical evidence, reliability, responsiveness, warranty, care and tariff simultaneously affect customer satisfaction in using JNE delivery services and partially physical evidence, reliability, responsiveness, care and tariffs have a significant effect on customer satisfaction, while the collateral variable does not have a significant effect on customer satisfaction in using JNE delivery services. The correlation coefficient value states that the relationship of free variables with bound variables is classified as very strong with a contribution of 58.1 %.